Participant Perspectives of Automated Short Messaging Service Interventions to Promote Physical Activity: A Systematic Review and Thematic Synthesis - Grobler, JS; Stavric, V; Saywell, NL (SAGE Publications, 2022)
Introduction Short messaging service has the potential to improve participation in physical activity in individuals with long-term health conditions. However, successful implementation relies on participant engagement with such programmes. The aim of this study was to undertake a systematic review of qualitative literature exploring participant perspectives of short messaging service-based interventions designed to promote physical activity for people with long-term health conditions. Methods CINHAL, MEDLINE, SPORTSDiscus, Scopus and Web of Science were searched up to 15 February 2021 looking for participants’ perspectives on short messaging service programmes designed to promote physical activity in people with long-term health conditions. Included studies were analysed using thematic synthesis. Results Eight studies involving 533 participants were included and analysed using the principles of thematic analysis and 10 descriptive themes were identified. These descriptive themes were further refined to develop five final analytical themes: taking control of my own health, from information to action, relationship with the programme, perfection required for success and increased expectations. Discussion The findings agree with published work on the factors which influence behaviour. The findings from this synthesis demonstrate that automated short messaging service programmes to increase physical activity are generally acceptable. People report that these interventions support and encourage physical activity. The novel finding of this study was that having more regular and long-lasting contact has the potential to increase the expectations people have of healthcare services. This is a finding which needs to be considered and managed but should not discourage the use of automated short messaging service.
Keywords: Participant perspectives; Automated messages; Physical activity; Qualitative; Meta-synthesis; Short messaging service